Analysis of Healthcare Workers' Behavior in Maternal and Child Health Services During the COVID-19 Pandemic in Aceh Province - Nurbaiti, Nurbaiti; Sari, Yuni (Journal of Health Science and Medical Therapy, 2024)
Healthcare workers, including midwives, face a high risk of disease, including the coronavirus. It is expected that healthcare workers possess good knowledge and behavior regarding the management of care for pregnant women, childbirth, newborns, and the handling of emergency complications during the COVID-19 pandemic. This study aims to explore the behavior of healthcare workers in providing health services to mothers and children during the COVID-19 pandemic. This descriptive study employs a cross-sectional design, involving all midwives in Aceh Province, with data collection conducted through Google Forms from June to July 2021. The results indicate that there is no relationship between age, length of service, and sources of health information with the behavior of healthcare workers in providing health services to mothers and children during the COVID-19 pandemic. However, there is a significant relationship between knowledge and COVID-19 prevention behavior, with a p-value of 0.000. In conclusion, healthcare workers with higher knowledge are more likely to exhibit good behavior in preventing the spread of COVID-19. Therefore, it is important to continue enhancing their knowledge, particularly regarding virus transmission, to strengthen supportive behaviors and contribute to breaking the chain of COVID-19 transmission.